Anticancer Activity of 1-r-2-([1,2,4]triazolo[1,5-c]-quinazoline-2-ylsulfanyl)etanon(ol)s - Yakymenko, M. O.; Antypenko, L. M. (Запорізький державний медичний університет, 2015)
Lately 2-thio-[1,2,4]triazolo[1,5-a]quinazolines were evaluated for in vitro anticancer activity against medulloblastoma (Daoy), hepatocellular carcinoma (HepG2) and melanoma (SK-MEL28) cell lines, whereas 3-(4-bromophenyl)-7-methyl-2-(2-(methylthio)-[1,2,4]triazolo[1,5-a]quinazolin-5-ylthio)quinazolin-4(3H)-one, 2-(methylthio)-[1,2,4]triazolo[1,5-a]quinazoline-5(4H)-thione and 5-chloro-2-(methylthio)-[1,2,4]triazolo[1,5-a]quinazoline and showed more potent activity than Dasatinib against Daoy cell.
Keywords: тези